A Randomized Control Study of Responsive Teaching With Young Turkish Children and Their Mothers. (May 2013) - Karaaslan, Ozcan; Diken, Ibrahim H.; Mahoney, Gerald
A randomized control study was conducted to evaluate the effectiveness of responsive teaching (RT) with a sample of 19 Turkish preschool-age children with disabilities and their mothers over a 6-months period. RT is an early intervention curriculum that attempts to promote children's development by encouraging parents to engage in highly responsive interactions with them. Participants were randomly assigned to treatment conditions: The control group consisted of standard preschool classroom services and the RT group received biweekly RT parent–child sessions in addition to standard services. Compared with the control group, RT mothers made significantly greater increases in Responsiveness and Affect, whereas their children made greater changes in their engagement or pivotal behavior. There were also significant group differences in children's developmental outcomes. Children in the RT group improved their developmental quotient scores by an average of 42% compared with 7% for children in the control group.